Trap-assisted tunnelling and Shockley-Read-Hall lifetime of extended defects in In.53Ga.47As p+n junction. (May 2019) - Hsu, P C (Brent); Simoen, E; Eneman, G; Merckling, C; Alian, A; Langer, R; Collaert, N; Heyns, M
Abstract: Several In.53 Ga.47 As p+n junctions with various extended defect densities (EDDs) have been grown by metalorganic vapor phase epitaxy (MOVPE), by carefully controlling the growth conditions. After fabrication, T-dependent J-V, C-V and double DLTS (DDLTS) are performed to extract the electrical field dependence of the extended defect levels. From this characterization, it is derived that the extended defects dominate the electrical field enhancement factor Г regardless of the value of the EDD and significantly increases the leakage current under reverse bias (i.e., decrease the Shockley-Read-Hall lifetime). These impacts are strongly connected to a "band-like" density of states of extended defects E2 at EC -0.32 eV by comparing the DDLTS and T-dependent J-V characteristics. On the other hand, the reference sample (without EDs) surprisingly exhibits an even stronger field dependence with lower leakage current. Nevertheless, no straightforward candidate point defects can be found in this sample and the possible explanation are discussed.